Pastoralists' indigenous selection criteria and other breeding practices of the long-horned Ankole cattle in Uganda - Kugonza, Donald R.; Nabasirye, M.; Hanotte, Olivier H.; Mpairwe, D.R.; Okeyo Mwai, Ally (Springer, 2012)
The criteria for identification, selection and kinship assignment of Ankole cattle and their roles to pastoralists were studied on 248 farms in Kiboga, Mbarara, Mpigi and Sembabule districts of Uganda using a questionnaire, administered during one-to-one interviews. Farms were randomly sampled along transects originating from the headquarters of each of the 19 sub-counties studied. We found that male Ankole cattle are reared for income from sales, meat for home use and ceremonies, aesthetic value and to maintain cultural heritage. Female cattle are mainly kept for milk production, income from sales, heritage and aesthetics, and in few cases, for home use as meat. Other functions included savings, manure and butter production. All cattle are named at birth with coat colour or pattern being the main identification criterion; hence, it is also useful in assigning kinship. Selection criteria for males are more stringent than for females. On most farms, all females are kept for further breeding and are only culled in cases of poor reproductive health. Primary emphasis in selecting males is on the performance of ancestors in milk and reproductive traits, and then on the qualities of the bull itself. Bulls are selected mainly focusing on a big body frame and size, horns that are white, large and curved upward and a plain dark red “ruhogo” coat colour. The results of this study show that pastoralists have a rich body of indigenous knowledge on this breed, and this should effectively be incorporated into planned selective improvement schemes of the Ankole cattle breed.